Assessment of some element content and potential health risks in infant formulas available in Turkish markets - Öztürk, Kübra; Caliskan, Cigdem Er; Akıncı, Zehra; Ciftci, Harun (My University, 2023)
Accurately determining the composition of essential and toxic elements in commercial infant formulas is critical to ensuring safe nutrition for infants. In this study, the concentrations of essential and toxic elements (Pb, Ni, Cd, Al, Cr, Cu, Fe, Mn, Zn, Co) in infant formulas were determined using high-resolution continuum-source flame atomic absorption spectrometry (HR-CS FAAS) and have been evaluated for health risk. The measured values for concentrations from lowest to highest were (in mg/kg): 36.38–77.45 (Zn), 6.28–12.88 (Al), 2.37–4.91 (Cu), 22.01–51.64 (Fe), and 0.55–2.06 (Mn). The highest concentrations of Ni and Cd were 0.18 and 0.09 mg/kg, respectively, while the lowest concentrations for these metals were below the detection limit. The Cr, Co and Pb levels were below the detection limits in all samples. According to the risk assessment conducted for infants aged 0–24 months, which involved calculating the estimated daily intake (EDI), the estimated weekly intake (EWI), the target hazard quotient (THQ), and the hazard index (HI), it was found that the THQ values range from 0.00 to 0.06 for Ni, from 0.00 to 0.69 for Cd, and from 0.17 to 0.22 for Al. However, since the HI for all age groups is less than 1, it can be concluded that there is no health concern for the elements Ni, Cr, Cd, Pb, Al, and Co.
Keywords: Infant Food; Element; FAAS; Health Risks